Teaching language and promoting citizenship - Hennebry, Mairin, 1979-; Gayton, Angela (Edinburgh textbooks in applied linguistics., 2019)
This book explores the relationship between language education and citizenship through theoretical and pedagogical lenses, examining existing language education provision in the context of the needs of today's learners and societies.